ASAL USUL KAMPUNG DULEL DI KECAMATAN ALOR BARAT DAYA DESA PROBUR KABUPATEN ALOR - Jefri Moban; Feni Diana Djaha, Selfius Kolihar, Serli Marlina Lahmau, Halena Muna Bekata, Petrus Mau Tellu Dony (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to determine the origin of Dulel Village in Alor Barat Daya Subdistrict, Probur Village, Alor Regency This research is a qualitative research method with an ethnographic approach. The methods used in this research are interviews and field observations. The results showed that the origin of the dulel village came from a man named Makna La who lived with his wife who came from the devil nation, finally Makna La and his wife destroyed the devil's village and lived happily and were blessed with two sons named Dulel and Madal, Dulel Village which was built by Dulel, named so that his descendants would not forget their origins. Based on the research results, it can be concluded that Dulel village has an origin related to the legend that developed in the local community.